Cerebrospinal Fluid Leak Rate after Vestibular Schwannoma Surgery via Middle Cranial Fossa Approach - Lipschitz, Noga; Kohlberg, Gavriel D.; Tawfik, Kareem O.; Walters, Zoe A.; Breen, Joseph T.; Zuccarello, Mario; Andaluz, Norberto; Dinapoli, Vincent A.; Pensak, Myles L.; Samy, Ravi N. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective Evaluate the cerebrospinal fluid (CSF) leak rate after the middle cranial fossa (MCF) approach to vestibular schwannoma (VS) resection.Design Retrospective case series.Setting Quaternary referral academic center.Participants Of 161 patients undergoing the MCF approach for a variety of skull base pathologies, 66 patients underwent this approach for VS resection between 2007 and 2017.Main Outcome Measure Postoperative CSF leak rate.Results There were two instances of postoperative CSF leak (3.0%). Age, gender, and BMI were not significantly associated with CSF leak. In the two cases with CSF leakage, tumors were isolated to the internal auditory canal (IAC) and both underwent gross total resection. Both CSF leaks were successfully treated with lumbar drain diversion. For the 64 cases that did not have a CSF leak, 51 were isolated to the IAC, 1 was located only in the cerebellopontine angle (CPA), and 12 were located in both the IAC and CPA. 62 patients underwent gross total resection and 2 underwent near-total resection. Mean maximal tumor diameter in the CSF leak group was 4.5 mm (range: 3–6 mm) versus 10.2 mm (range: 3–19 mm) in patients with no CSF leak (p = 0.03).Conclusions The MCF approach for VS resection is a valuable technique that allows for hearing preservation and total tumor resection and can be performed with a low CSF leakage rate. This rate of CSF leak is less than the reported rates in the literature in regard to both translabyrinthine and retrosigmoid approaches.
Keywords: vestibular schwannoma; middle cranial fossa; cerebrospinal fluid leak; complication